Reducing Status Quo Bias in Choice Experiments - Ole Bonnichsen; Jacob Ladenburg (University of Oslo, 2015)
To secure the validity and applicability of stated preference measures in economic analysis, hypothetical preferences must mimic real life preferences. For instance, people have a propensity to prefer what they already have when presented with alternatives that, all things being equal, seem to be superior, i.e. a status quo effect. However, in the stated preference literature, the tendency to choose the alternative representing the status quo situation seems to exceed real life status quo effects. Accordingly, status quo bias can be a problem. In the Choice Experiment literature, status quo bias is found to be a function of protest attitudes concerning the payment of the hypothetical good. In a split sample framework we test an ex-ante entreaty aimed at reducing payment based protest attitudes. We find that the entreaty reduces status quo bias and improves the internal validity of stated preferences in our data based on Swedish ostomates' preferences for ostomy pouch quality changes.  Published: Online January 2015. In print December 2015.